Xylo-oligosaccharides improve the adverse effects of plant-based proteins on weaned piglet health by maintaining the intestinal barrier and inhibiting harmful bacterial growth - Wang, Qibing; Zhao, Yang; Guo, Lei; Ma, Xiangyuan; Yang, Yi; Zhuo, Yong; Jiang, Xuemei; Hua, Lun; Che, Lianqiang; Xu, Shengyu; Feng, Bin; Fang, Zhengfeng; et al. (Frontiers in Microbiology, 2023)
Piglets are more susceptible to weaning stress syndrome when fed high levels of plant-based proteins that contain abundant food antigens and anti-nutritional factors. Xylo-oligosaccharides (XOS) is a potential prebiotic that may improve the tolerance of weaned piglets to plant-based proteins. The aim of this study was to investigate the effects of XOS supplementation in high- and low plant-based protein diets on the growth performance, gut morphology, short-chain fatty acid (SCFA) production, and gut microbiota of weaned piglets. A total of 128 weanling piglets with an average body weight (BW) of 7.63 ± 0.45 kg were randomly allocated to one of four dietary treatments in a 2×2 factorial arrangement, with two levels of plant-based proteins (d 1-14: 68.3% or 81.33%, d 15-28: 81.27% or 100%) and XOS complex (0% or 0.43%) over a 28-day trial. The growth performance of piglets did not differ significantly among groups (P > 0.05). However, the diarrhea index of weaned piglets fed a high plant-based protein diet (HP) was significantly higher than that of those fed a low plant-based protein diet (LP) at days 1-14 and throughout the experimental period (P < 0.05). XOS treatment tended to reduce the diarrhea index at days 1-14 (P = 0.062) and during the whole experiment period (P = 0.083). XOS treatment significantly increased the digestibility of organic matter at days 15-28 (P < 0.05). Moreover, dietary XOS supplementation increased ileal mucosa mRNA expression of occludin and ZO-1 (P < 0.05). Furthermore, the concentration of butyric acid (BA) in cecal contents and the concentrations of BA and valeric acid (VA) in colon contents were significantly elevated in XOS groups (P < 0.05). Additionally, XOS optimized the gut flora by lowering the number of pathogenic bacteria such as p_Campylobacterota, thereby stabilizing the gut ecosystem. In conclusion, HP diet aggravated diarrhea in weaned piglets while XOS alleviated it by improving nutrient digestibility, protecting intestinal morphology, and optimizing the gut flora.